Assessment of risk factors for developmental delays among children in a rural community of North India: A cross-sectional study - Neha Sharma; Jamal Masood; S N Singh; Naim Ahmad; Prabhaker Mishra; Shikhar Singh; Sudip Bhattacharya (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Initial formative years in every children's life are critical for their optimal development, as these frame the foundation of future well-being. With a varied prevalence of developmental delays (DDs) in the world and most of the studies representing the hospital-based data. The present study was aimed to find the prevalence and risk factors for DDs (domain wise) in children aged 2 months to 6 years in the rural area of North India. METHODS: This was a cross-sectional study in which a multistage random sampling technique was used. From 30 Anganwadi centers, 450 children aged 2 months-6 years were taken in the study. Rashtriya Bal Swasthya Karyakram screening tool developed by the Ministry of Health and Family Welfare, India, was used for developmental screening. Binary logistic regression analysis was done to identify the predictors for DDs (domain wise). RESULTS: Seventy-three (16.2%) children were found to have DDs and 60 (13.3%) children had the global DDs. About 84/421 (20.0%) children had cognitive delay, followed by 43/450 (9.6%) children who had delay in speech and language area. About 17/190 (8.9%) children had social delay while 26/407 (6.4%) children had hearing and vision impairment. Gross motor delay was seen in 24/450 (5.3%) children and 16/300 (5.3%) children had fine motor delay. Gestational age (adjusted odds ratio [AOR] - 13.30), complications during delivery (AOR - 25.79), meconium aspiration (AOR - 12.81), and child never breastfed (AOR - 8.34) were strong predictors for the delay in different domains of developmental milestones. CONCLUSION: Socio-economic, ante-natal, natal and post-natal factors should be considered for prompt identification and initiation of intervention for DDs. RECOMMENDATION: There is a need for increasing awareness and knowledge of parents regarding the achievement of developmental milestones according to the age. A multipronged approach to the holistic treatment of developmentally delayed children for early intervention is required.